Arresting the phenomenon of heater flooding in a wickless heat pipe in microgravity. (June 2016) - Kundan, Akshay; Nguyen, Thao T.T.; Plawsky, Joel L.; Wayner, Peter C.; Chao, David F.; Sicker, Ronald J.
Highlights: Flooding limitation is observed and explained in 40 mm microgravity heat pipe. A new phenomenon is observed that arrests the growth of flooding limitation. Arresting is caused by balancing of Marangoni stress and capillary pressure gradient. Arresting behavior verified by temperature based 1D heat transfer models. Interfacial forces creates superheated vapor region and condensation at hot end. Abstract: The Constrained Vapor Bubble (CVB) is a transparent, wickless heat pipe experiment carried out in the US Labs of the International Space Station (ISS). Experiments were carried out using the 40 mm CVB, 3 mm× 3 mm in cross-section, pentane as the working fluid, with the power inputs of up to 3 W. Due to the low Bond number (Bo) in microgravity and materials of construction, the CVB system was ideally suited to determine the contribution of the Marangoni forces toward the limiting heat pipe performance, and the transparent quartz shows exactly how that limitation occurs. Previous literature models and experimental temperature and pressure measurements suggested that at high enough temperature gradients, the working fluid should be subjected to enough Marangoni force to force it away from the heater and ultimately, dry out the hot end. The CVB experiment shows that high temperature gradients lead to a totally opposite behavior, i.e., 'flooding' of the heated end. Flooding of the heater end is attributed to a competition between Marangoni-induced flow due to high temperature gradients at the heater end and capillary return flow from the cooler. This creates a thick liquid layer in the corner of the cuvette at the heater end. At the point of flow balance, a thick layer of liquid is observed on the flat surface of the quartz cuvette. This is defined as the central drop. The region from the top of the heater end to the central drop is referred to as the interfacial flow region. The interfacial flow region develops at a power input of around 0.7 W, and increases in length to the power input of 2 W. At 2 W, the strength of the Marangoni forces saturate. As a result, the forces in the flooded interfacial region are not able to push the liquid further into the capillary region and a further penetration of liquid down the axis of the heat pipe is arrested. As the power input is increased to nearly 3 W, an increase in the vapor space is observed near the heater end at 3 W. This behavior suggests that the flooding might just be an intermediate stage in reaching the dry-out limitation. The flat quartz surface at the hot end is covered by a wavy thin liquid film due to the interfacial forces. The hot end region closest to the heater is a superheated vapor region that leads to the condensation. This additional observation is discussed in Appendix.